2005
DOI: 10.1158/1078-0432.ccr-05-1274
|View full text |Cite
|
Sign up to set email alerts
|

Specialized DNA Arrays for the Differentiation of Pancreatic Tumors

Abstract: Purpose: Malignant tumors of the pancreas are frequently indistinguishable from inflammatory tumors arising in the context of a chronic pancreatitis with the use of conventional imaging techniques. Thus, cytologic analysis of cells obtained by abdominal ultrasound, computed tomography, or endoscopic ultrasound^guided fine needle aspiration biopsy is required for diagnosis. However, the reliability of cytologic analyses of pancreatic fine needle aspirates remains unsatisfactory, with a diagnostic accuracy of V8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 23 publications
2
25
0
1
Order By: Relevance
“…Annexin A2-Overexpression of annexin A2 in pancreatic cancer has been reported previously (4,7,12,21,22). Our data in this study revealed that annexin A2 is not overexpressed in the primary chronic pancreatitis: the expression ratio of annexin A2 in chronic pancreatitis compared with normal pancreas is 1.1-fold.…”
Section: Figsupporting
confidence: 72%
“…Annexin A2-Overexpression of annexin A2 in pancreatic cancer has been reported previously (4,7,12,21,22). Our data in this study revealed that annexin A2 is not overexpressed in the primary chronic pancreatitis: the expression ratio of annexin A2 in chronic pancreatitis compared with normal pancreas is 1.1-fold.…”
Section: Figsupporting
confidence: 72%
“…In order to circumvent both of these problems, we have previously designed a specialized 588-feature cDNA array for pancreatic cancer differential diagnosis. In a proof-of-principle study with 62 pancreatic tissue samples, including 16 FNAB samples, we demonstrated that a 169-gene expression signature obtained with this array in conjunction with a specifically developed classification algorithm is suitable to distinguish between PDAC and nonmalignant processes with 1 95% diagnostic accuracy [86] ( fig. 2 ).…”
Section: Multiclass Diagnosismentioning
confidence: 96%
“…The classifier was then evaluated using the independent 20-sample test set, demonstrating 6 95% diagnostic accuracy (right panel: one benign control sample is falsely classified as PDAC). Modified from Buchholz et al [86] . However, the use of large scale ('whole genome') arrays is extremely costly and generates vast amounts of data which are difficult to analyze in a routine diagnostic setting.…”
Section: Multiclass Diagnosismentioning
confidence: 99%
“…Our second data set comes from gene expression profiles from the pancreas (see Buchholz et al [12]). This data set provides two classes (pancreas cancer vs. pancreatitis/normal) for 62 samples.…”
Section: Data Setsmentioning
confidence: 99%